2016
DOI: 10.1128/mbio.00436-16
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factor KLF2 in Dendritic Cells Downregulates Th2 Programming via the HIF-1α/Jagged2/Notch Axis

Abstract: The adaptive immune response is tightly regulated by complex signals in dendritic cells (DCs). Although Th2 polarization is dictated by defined functional DC subsets, the molecular factors that govern the amplitude of these responses are not well understood. Krüppel-like factor 2 (KLF2) is a transcription factor that negatively regulates the activation of numerous immune cells in response to stimuli. Here, we demonstrate that suppression of KLF2 in conditioned DCs preferentially amplifies Th2 responses in two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 41 publications
(54 reference statements)
0
13
0
Order By: Relevance
“…The significant down-regulation of klf2 and klf4 detected in both in vivo challenge and field samples, indicates a function in cell cycle arrest of these genes in AGD. KLF2 is also involved in immunity and suppression of KLF2 in dendritic cells has been reported to amplify Th2 responses 75 . In addition, KLF2 has been described to inhibit pro-inflammatory activation of monocytes in mammals 76 and in fish 77 .…”
Section: Discussionmentioning
confidence: 99%
“…The significant down-regulation of klf2 and klf4 detected in both in vivo challenge and field samples, indicates a function in cell cycle arrest of these genes in AGD. KLF2 is also involved in immunity and suppression of KLF2 in dendritic cells has been reported to amplify Th2 responses 75 . In addition, KLF2 has been described to inhibit pro-inflammatory activation of monocytes in mammals 76 and in fish 77 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, there are several reports showing upregulation of Th2 transcription factor GATA3 through IL-4 by activating STAT5 and STAT6 transcription factors (TFs), but few of them indicate that GATA3 expression can be independent of IL-4 as well ( 28 , 30 ). Apart from signaling molecules, it has been reported that IRF4 depleted DCs are unable to induce Th2 differentiation ( 28 , 31 , 32 ), whereas increased KLF2 in DCs negatively regulates Th2 induction ( 33 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the role of Notch signaling in T cell responses is clearly unique to pathogen type and not easily predicted. Enhanced accumulation of Jagged 2-expressing DC due to KLF2 deficiency augmented the non-protective IL-4 response to H. capsulatum (54), supporting a role for Notch in shaping T cell responses to fungal infection. However, the effects of canonical Notch signaling on protective T cell responses necessary for fungal clearance are unknown.…”
Section: Introductionmentioning
confidence: 92%